THE THEORETICAL MODEL OF USING STATISTICAL METHODS IN THE EVALUATION OF THE FINANCIAL SITUATION OF THE TRANSPORT UNDERTAKING - Gazdikova, Jana; Sustekova, Daniela (Doprava a spoje, 2012)
The paper deals with the use of statistical methods in analyzing the company's financial situation. There are defined and justified the appropriate methods and procedures for forming the proposed model.